"Treasures from the Wreck of the Unbelievable" - archeologia jako element strategii artystycznej Damiena Hirsta - Brillowski, Wojciech (Artium Quaestiones, 2020)
The most important element of Damien Hirst's multimedia project "Treasures from the Wreck of Unbelivable" was the exhibition, presented from April 9 to December 3, 2017 in Venice, in the galleries of the Pinault Foundation in Punta della Dogana and Palazzo Grassi. It was completed by several book publications and a 90-minute film of the same title, made available globally on the Netflix online platform on January 1, 2018. The exhibition included over a hundred objects, mainly sculptures, made in various techniques and materials in a wide range of sizes. The film, stylized as a popular science documentary, presents the fictional story of their discovery and exploration at the bottom of the Indian Ocean, and their transport to Venice. It develops the main idea of the exhibition – a fictitious vision of the origin of these objects from an ancient wreck, filled with artistic collections, belonging to a fabulously rich ancient Roman freedman, with the significant name Cif Amotan II (anagram from “I am a fiction”). Realizing this fancy artistic vision, most of the works were made as if they had been damaged by the sea waves and overgrown with corals and other marine organisms. Hirst created a comprehensive and all-encompassing narrative using the principle of "voluntary suspension of unbelief," formulated by Samuel T. Coleridge. The artist sets himself and the viewer on a fantastic journey into the ancient past, taking up subjects central to his ouevre for decades: faith, relations of art and science, transience and death. He does this by means of numerous references to the artistic and mythological heritage of antiquity, not only Graeco-Roman, but also of other great cultures and civilizations. Although the formal and technical aspects of the project will also be discussed, the main goal of the author is to analyze how Hirst used the knowledge of antiquity (classics) to create both the exhibition itself and the mockumentary. The artist made archeology an element binding his narrative together, showing in the film not only how artefacts were obtained from the bottom of the ocean. He also presented a number of tasks that scientists deal with at various stages of the project – from the first discovery, through interpretation and conservation, to the presenting at the museum-like exhibition. Of course, his purpose was not to create a study in the methodology of underwater exploration, but to reflect on the cognitive power of science examining remains of ancient times. By juxtaposing two possible attitudes towards relics of the past, i.e. the strict discipline of the scholar and the imagination of the treasure hunter, he concludes that narratives arising from them will both have the character of a mythical tale. The ontic status of the artefacts themselves, as the things of the past, left in a fragmentary state by the passage of time, sets all the stories related to them within the discourse of faith.